2021
DOI: 10.3389/fpubh.2021.715904
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 Pandemic in High Income Countries Such as Canada: A Better Way Forward Without Lockdowns

Abstract: The SARS-CoV-2 pandemic has caused tragic morbidity and mortality. In attempt to reduce this morbidity and mortality, most countries implemented population-wide lockdowns. Here we show that the lockdowns were based on several flawed assumptions, including “no one is protected until everyone is protected,” “lockdowns are highly effective to reduce transmission,” “lockdowns have a favorable cost-benefit balance,” and “lockdowns are the only effective option.” Focusing on the latter, we discuss that Emergency Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 105 publications
(156 reference statements)
0
33
0
Order By: Relevance
“…In general, these studies have limitations given that no randomized trial has assessed this question and modeling, or observational studies leave substantial uncertainties and are subject to selective reporting and interpretation (227). A meta-analysis has found very small benefits of lockdowns on COVID-19 mortality rates (16), and cost-benefit analyses find that the costs of lockdowns (including what we outline above) far outweigh any potential benefit that may occur (6,228). Debate and disagreement will likely continue, given that assessments on the relative benefits of lockdown are based largely of weak observational data under very complex circumstances.…”
Section: Rising Inequalitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, these studies have limitations given that no randomized trial has assessed this question and modeling, or observational studies leave substantial uncertainties and are subject to selective reporting and interpretation (227). A meta-analysis has found very small benefits of lockdowns on COVID-19 mortality rates (16), and cost-benefit analyses find that the costs of lockdowns (including what we outline above) far outweigh any potential benefit that may occur (6,228). Debate and disagreement will likely continue, given that assessments on the relative benefits of lockdown are based largely of weak observational data under very complex circumstances.…”
Section: Rising Inequalitiesmentioning
confidence: 99%
“…Studies that suggest substantial benefits of lockdown, typically have flaws or limitations that seriously question the validity, e.g., their counterfactual is based on tenuous assumptions in forecasting models ( 88 ), they use interrupted time-series designs without a stable long-term period before and after intervention and without controlling for confounders ( 89 , 90 ), and/or have no control non-intervention group (i.e., not a difference-in-difference approach) ( 89 , 90 ), and other flaws ( 16 ). Furthermore, it was shown that lockdowns were very costly economically, but probably did not save lives ( 6 , 91 ). Despite this, citizens generally believed many unfounded COVID-19 scientific claims leading to strong support of NPIs ( 92 ).…”
Section: Psychological Tacticsmentioning
confidence: 99%
See 3 more Smart Citations